Pandemic Economic Growth Recovery Strategies: Strengthening Village Potentials in The Agricultural Sector Sustainable Farming - warda, warda (Inovbiz: Jurnal Inovasi Bisnis, 2024)
The purpose of this study is "To find out the post-pandemic economic growth recovery strategy through strengthening the potential of the village in the agricultural sector. The research method used in this study is a qualitative descriptive method using an evaluative approach based on research data analysis using a SWOT matrix analysis. This analysis is suitable for determining economic recovery strategies by taking into account the strengths and weaknesses of the agricultural village potential and taking into account external opportunities and threats. The results of the analysis conclude that: a) Strategic application of sustainable farming methods (sustainable farming) is needed in order to deal with the problems of threats faced by farmers caused by a decrease in the quality of soil fertility due to excessive use of fertilizers so that production levels decrease. b) Government policy strategies are needed in the practice of improving post-pandemic economic practices, namely that business people and the government can operate responsibly to gain profits. So that farmers can benefit more from their crops and be more active after their income decreases during a pandemic, so the government can benefit from reducing the cost of rice imports. c) The government needs to carry out a strategy for optimizing the strengthening of village potential in the agricultural sector because villages have sufficient potential because the land in the village is still very large and is indeed suitable for agriculture. With efforts to focus on optimizing village farmers, the welfare of farmers who have so far been under-empowered can improve. They will get the opportunity to further develop with the support and attention from the government. d) Technology application strategy for agriculture so that agricultural products are of the best quality and quantity because actually the high public consumption of food needs is getting higher post-pandemic.